The Importance of Intonation in The Performance of Different Speech Acts - Alsmadi, Khalid Ahmad; Yunus, Kamariah; Almadani, Yasmeen (English Education: Jurnal Tadris Bahasa Inggris, 2020)
There are many pieces of substantial evidence that many world languages employ intonation to perform a lot of daily life actions. Recent studies indicate that intonation is part and parcel of any practical analysis of linguistic components. However, it was only in 1990s until we start to see studies on intonation and speech act. The link between intonation and speech act has not met the required attention. Moreover, lack of sufficient knowledge about the correct use of intonation among non-native English language speakers shows non-native like English proficiency among them. This then may have effects on the teaching and learning of the English language on students. The study aims at examining the role intonation plays in the performance of different speech acts. Thus, the paper provides a further explanations and illustrations to understand the role intonation has in speech act theory.